Little monsters - Johnson, Nicole (Writer of children's books); Roxburgh, Ricky; Gannaway, Bobs (2022)
A story based on an episode of the Disney animated show "Monsters at Work" follows Tylor Tuskmon, who hopes to imitate his idols, Mike and Sully, and become a Jokester on the Monsters, Inc. Laugh Floor.
Keywords: Monsters -- Juvenile fiction; Occupations -- Juvenile fiction; Joking -- Juvenile fiction; Monsters -- Fiction; JUVENILE FICTION / Media Tie-In.; JUVENILE FICTION / Monsters; JUVENILE FICTION / Reader - Beginner; Joking; Monsters; Occupations; Children's stories; Readers (Elementary); Fiction; Juvenile works; Picture books; Readers (Publications); Readers (Publications); Picture books